2023
DOI: 10.1186/s12284-023-00623-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-environment Genomic Selection in Rice Elite Breeding Lines

Abstract: Background Assessing the performance of elite lines in target environments is essential for breeding programs to select the most relevant genotypes. One of the main complexities in this task resides in accounting for the genotype by environment interactions. Genomic prediction models that integrate information from multi-environment trials and environmental covariates can be efficient tools in this context. The objective of this study was to assess the predictive ability of different genomic pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Selection intensity ( i ) and accuracy ( r ) have been improved by integrating the genomic selection in the breeding program, selecting and advancing the lines based on the breeding values rather than phenotypic BLUPs (Heffner et al 2009 ; Jannink et al 2010 ; Desta and Ortiz 2014 ; Crossa et al 2017 ; Chung and Liao 2020 , 2021; Dreisigacker et al 2023b ). Replicated experimental designs with robust analysis based on mixed-model approaches accounting for spatial trends and G x E interactions have been incorporated into the program to improve heritability and selection accuracy (Voss-Fels et al 2018 ; Cooper et al 2020 ; Xu et al 2020 ; Cooper et al 2021 ; Xu et al 2022 ; Cooper et al 2023 ; Nguyen et al 2023 ). In the future, the salinity breeding program is targeting to move to a 2-year breeding cycle by integrating genomic selection with speed breeding and early recycling of the genotypes (Jighly et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Selection intensity ( i ) and accuracy ( r ) have been improved by integrating the genomic selection in the breeding program, selecting and advancing the lines based on the breeding values rather than phenotypic BLUPs (Heffner et al 2009 ; Jannink et al 2010 ; Desta and Ortiz 2014 ; Crossa et al 2017 ; Chung and Liao 2020 , 2021; Dreisigacker et al 2023b ). Replicated experimental designs with robust analysis based on mixed-model approaches accounting for spatial trends and G x E interactions have been incorporated into the program to improve heritability and selection accuracy (Voss-Fels et al 2018 ; Cooper et al 2020 ; Xu et al 2020 ; Cooper et al 2021 ; Xu et al 2022 ; Cooper et al 2023 ; Nguyen et al 2023 ). In the future, the salinity breeding program is targeting to move to a 2-year breeding cycle by integrating genomic selection with speed breeding and early recycling of the genotypes (Jighly et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Literature indicates that including environmental covariates is not always advantageous. For instance, Monteverde et al (2019); Nguyen et al (2023) reported that adding environmental covariates resulted in worse predictions than GBLUP in rice while predicting new environments, which could be attributed to higher inter-environmental differences. In the studies predicting new genotypes, Jarquín et al (2014); Malosetti et al (2016) and Rincent et al (2019) observed little to no improvement with a GxW model.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Monteverde et al (2019); Nguyen et al (2023) reported that adding environmental covariates resulted in worse predictions than GBLUP in rice while predicting new environments, which could be attributed to higher inter-environmental differences. In the studies predicting new genotypes, Jarquín et al ( 2014…”
Section: Gxe-blup and Gxw-blup Models Are Useful For Predicting Grain...mentioning
confidence: 99%
“…Furthermore, it has been shown that agronomic management and environmental factors influence Zn uptake, translocation, and loading into grains and that seasonal effects possibly linked to water supply and soil redox state further affect [Zn] in grains ( Goloran et al., 2019 ; Inabangan-Asilo et al., 2019 ). For grain yield, extensive genotype × environment interactions (GEI) are common in rice ( Huang et al., 2021 ; Nguyen et al., 2023 ), and this necessitates multi-environment trials (METs) during variety development. Since GEI is only important when it causes significant changes in genotypic rankings in different environments, it is important for the efficacy of a breeding program to obtain estimates of the strength of GEI effects relative to genotype (G) and environment (E) effects.…”
Section: Introductionmentioning
confidence: 99%